Antihypertensive therapy and left ventricular hypertrophy prevention in patients with essential arterial hypertension and high treatment compliance - N. A. Koziolova; I. M. Shatunova; I. A. Lazarev (Кардиоваскулярная терапия и профилактика)
Aim. To investigate the features of antihypertensive therapy (AHT), as a method of left ventricular hypertrophy (LVH) prevention, in patients with essential arterial hypertension (EAH), absence of target organ damage (TOD), and high treatment compliance. Material and methods. This prospective cohort study included 428 patients with EAH and no TOD (mean followup 8,8±2,6 years). Results. In patients with EAH, and high treatment compliance, LVH incidence was 36,9 %. AHT was more aggressive in patients with LV remodelling, and was characterised by higher rates of combined treatment or b-adrenoblocker treatment. Conclusion. In EAH patients with high treatment compliance, LVH incidence was lower than in general population. More aggressive AHT among patients with LVH could be explained by potential therapy resistance in this clinical group.